Thinking locally, acting globally? Stakeholder conflicts over UNESCO World Heritage inscription in Western Australia. - Jones, Roy; Shaw, B. (Routledge, 2012)
This study will evaluate three World Heritage initiatives in Western Australia; Shark Bay and Ningaloo Reef, both isolated and near-pristine natural areas, and Fremantle, a historic townscape within a large metropolitan region. In all the three cases, sections of the local communities have campaigned against World Heritage designation, not because they failed to see the heritage value of the areas under consideration, but because they saw the ‘fallout’ from such designations as a threat to various aspects of their ways of life. A range of official, academic and media sources and direct input from stakeholders are used to illustrate issues of concern and, on occasion, conflict at these three sites. While this was clearly not the intention of those seeking the World Heritage designations, sections of the community at all three locations feared that such designations would exacerbate, rather than ameliorate, what they saw as the negative impacts of the rapid social and economic changes that are, in any case, occurring across the state.